(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Aim: This study aimed to evaluate the thyroid profile in patients with liver cirrhosis and to correlate the findings with the severity and etiology of the underlying liver disease. Methods: This cross-sectional, observational study was conducted on 74 patients diagnosed with liver cirrhosis. Serum levels of Triiodothyronine (T3), Thyroxine (T4), and Thyroid Stimulating Hormone (TSH) were estimated. The severity of liver disease was assessed using the Child-Pugh score. Patients were categorized by etiology (alcoholic, viral, and cryptogenic/other). Statistical analysis was performed using ANOVA and Pearson’s correlation coefficient to determine associations. Results: The study population (n=74) had a mean age of 54.2 ± 9.8 years. A significant decline in mean T3 levels was observed with increasing severity of cirrhosis (Child-Pugh A: 1.12 ng/mL, B: 0.73 ng/mL, C: 0.45 ng/mL; p<0.001). Low T3 syndrome was the most common abnormality, present in 70.2% of patients. There was a significant negative correlation between Child-Pugh score and T3 levels (r = -0.752, p<0.001). T4 levels also decreased with worsening disease, but the correlation was weaker (r = -0.451, p<0.05). TSH levels remained within the normal range in most patients and did not correlate with severity. While alcoholic cirrhosis was associated with the lowest T3 levels, the difference between etiological groups was not statistically significant (p=0.08). Conclusion: Low T3 syndrome is highly prevalent in liver cirrhosis and demonstrates a strong, inverse correlation with disease severity. This makes serum T3 a reliable biochemical marker for assessing the severity of hepatic dysfunction. Thyroid hormone derangements in cirrhosis are primarily a reflection of hepatic functional reserve rather than the specific etiology of the disease.